Morphology and taxonomy of Isognomon spathulatus (Reeve, 1858), a cryptic bivalve from the mangroves of Thailand - Tëmkin, Ilya; Printrakoon, Cheewarat (Zootaxa, 2016)
Isognomon spathulatus (Reeve, 1858) is redescribed based on type material and original collections from Kungkrabaen Bay, Thailand. The species agrees with previously described isognomonids in most conchological and anatomical features, but possesses a suite of diagnostic characters, including a comma-shaped outline of the nacreous border, an uncoiled ventral diverticulum of the stomach, and the thickened mantle lobes with granulated cells. This study is the most comprehensive morphological analysis to date for any species of Isognomonidae Woodring, 1925 (1828). It describes and illustrates a number of previously unrecognized or underutilized anatomical characters of potential phylogenetic significance: the morphology of the byssal threads (cross-sectional shape, plumate rootlets, and the shape of adhesive disks), the presence and extent of the interdemibranchial buttresses, the presence of secretory cells in the central zone of the mantle, the shape of the ventral diverticulum of the gastric chamber, the presence of the typhlosolar guard ridge, and the position of the renal pore. A comparison is made between I. spathulatus and morphologically similar Isognomon ephippium (Linnaeus, 1758) with which it has been previously synonymized. Pearls of both species are described and illustrated. Individuals of I. spathulatus inhabit mangroves, where they attach by byssus to prop roots, typically in parapatry with individuals of I. ephippium that occupy adjacent mudflats. The spacial distribution and diverging adaptive strategies (pertaining to physical stabilization and response to predation) displayed by the two isognomonid species are considered in the light of the ecological speciation theory.